Modelling engineered barriers for spent nuclear fuel repository using a double-structure model for pellets. Issue 1 (3rd May 2018) - Toprak, Erdem; Olivella, Sebastia; Pintado, Xavier
Abstract : This paper describes an experimental programme and the corresponding modelling in order to characterise the hydromechanical (HM) behaviour of pellets. At least two levels of porosity can be distinguished in the pellets: microporosity and macroporosity. In general, the microstructure is associated with the active clay minerals, while the macrostructure accounts for the larger-scale structure of the material. In pellets, this concept can be somewhat different as a pellet arrangement creates a large-scale macropore structure. The Barcelona expansive model is proposed to reproduce the material response through infiltration and oedometer tests. In addition to expansive model parameters, a set of hydraulic laws considering the double-structure phenomenon is necessary to perform HM analysis. This paper also describes the effect of macroporosity on the intrinsic permeability changes. To illustrate the general objectives of this research, a full-scale thermohydromechanical calculation has been done to show the capabilities of the approach. The Barcelona basic model (for clays) and Barcelona expansive model (for pellets) have been used in this full-scale calculation.